Mechanism and prevention measures of asymmetric floor heave in mining roadway of Huipodi Coal Mine - Zhao Hongbao; Liu Yihong; Cheng Hui; Li Jinyu; Xu Jianfeng; Wang Yikuo (矿业科学学报, 2020)
Taking Huipodi coal mine as the engineering background, the asymmetric deformation mechanism of the mining roadway under the island coal pillar was studied by theoretical analysis, numerical simulation and field measurement, and the corresponding floor heave prevention and control measures were proposed.The results show that the rock mass below the island coal pillar has the characteristics of zoning failure and is mainly shear failure, while the rock mass below the mined area is mainly tensile failure, and the rock mass failure morphology is inverted trapezoid.Roadway 11-1021 is located at the junction of shear failure and tensile failure rock mass, which results in different degrees of damage and damage of the surrounding rock on both sides of the roadway, so the roadway exhibits asymmetric deformation characteristics, that is, the rock of roadway near the coal pillar side has a large internal stress and a small amount of deformation, while the stress near the goaf side rock is small and the floor heave is large.Based on the stress and deformation distribution characteristics of the surrounding rock on both sides of the roadway, a floor heave prevention and control technology based on the idea of anti-binding is put forward and verified on site.The results show that when the roadway is not affected by the mining, the floor heave volume of the area treated by the floor heave prevention measures is greatly reduced, and the drum speed tends to be stable with time; when the roadway is affected by the mining, the amount of floor heave in the treatment area of the control measures was reduced by nearly 1/2, meeting the production requirements.